PENERAPAN PENDEKATAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Hafsah Puspita Dewi; Elsa Fitri; Eva Dwi Minarti (IKIP Siliwangi, 2018)
This study aims to know the achievement of the ability of the solution of the problems a useful or valuable junior high school students who used the realistic mathematics conventional by learning, the experimental work on this , matter used arithmetic is social class VII junior high school semester the even. Methods used is quantitative, who is in the form of experiments in supported by data from pretes and postes.The population research is junior high school students class VII in west bandung.With 43 sample graders experiment and 40 graders controls on the academic year 2017 / 2018. An instrument that is used is math tests the ability of the solution of the problems .Processing the data were analyzed using ibm spss version 21 application statistics . Processing data using analysis test normality and has been continued by test the average namely mann-whitney test .Based on the analysis conducted , results showed that the achievement of the ability of the solution of the problems a useful or valuable junior high school students who used the mathematics realistic better than conventional learning .